Development of Open Switch Fault-Tolerant Capability in CCS-MLI Topology - Kumar, Dhananjay; Nema, Rajesh Kumar; Gupta, Sushma; Dewangan, Niraj Kumar (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2022)
Multilevel inverters (MLIs) are very popular in renewable energy applications and other DC to AC conversion systems due to their reliability, reduced voltage stress, low total harmonic distortion (THD), reduced filter size, low electromagnetic interference, etc. Consequently, the photovoltaic (PV) generation systems, mainly installed in remote areas, require highly reliable systems. The high failure rate of sources and power semiconductor devices results in very low reliability for inverters used in PV generation systems. The aim of this study is to develop a five-level MLI topology with fault-tolerant (FT) characteristics. Therefore, a highly resilient fault-tolerance topology, based on a cross-connected source-based MLIs (CCS-MLI) structure, is proposed in this paper. The developed CCS-MLI topology can tolerate open switch faults in any single switch failure. The proposed system and results developed in a MATLAB/Simulink environment are discussed under normal and faulty states. The simulation results are validated experimentally. Finally, the quantitative and qualitative superiority of the proposed CCS-MLI is demonstrated through the comparative analysis of other recent topologies.